Application of family-involved smart medication management system in rural-dwelling middle-aged and older adult participants with chronic diseases: Management of chronic diseases in rural areas. Issue 45 (11th November 2022) - He, Jiankang; Chen, Jinjin; Li, Qianqian; Yang, Zhipeng; Liang, Huan; Wang, Lu; Sun, Zhixia; Zhao, Huaijun
Abstract : Management of patients with chronic diseases in rural areas and the use of medications need to be urgently addressed. Therefore, this study aimed to evaluate the efficacy of a family-involved smart medication management system for rural patients with chronic diseases. Between June and August 2021, 82 patients with chronic diseases were selected using convenience sampling from 2 county towns in Hebei Province, China. They were randomly divided into control (41 participants) and experimental (41 participants) groups. The control group was managed using a routine medication management model for chronic diseases. The experimental group was managed using a family-involved smart medication management system, in addition to the control group interventions. The groups were graded using the 8-item Morisky Medication Adherence Scale (MMAS-8), the Self-efficacy for Appropriate Medication Use Scale (SEAMS), the Medication Knowledge Assessment Questionnaire, and the Family Support Scale before the intervention and at 8 and 24 weeks after the intervention. Pre-intervention group differences were not statistically significant. At 8 weeks after the intervention, the control group showed no statistically significant differences in the MMAS-8, SEAMS, and Medication Knowledge Assessment scores pre-and post-intervention. These scores were higher in the experimental group than in the control group, with the post-intervention scores being higher than the pre-intervention scores. The MMAS-8, SEAMS, and Medication Knowledge Assessment scores for the experimental group were higher at 24 weeks than at 8 weeks; these scores were higher in the experimental group than in the control group. The experimental group also had higher family support scores than the control group; these scores were higher pre-intervention than post-intervention. A family-involved smart medication management system can effectively improve medication adherence, self-efficacy for appropriate medication use, medication knowledge assessment scores, and family support for rural middle-aged and older adult patients with chronic diseases.